Diet and Culture Exchange between Central Plains and Turpan during Tang Dynasty - Chen, Songlin (International Journal of Social Sciences and Public Administration, 2024)
The culinary culture of the Tang Dynasty was extremely prosperous, with a wide variety of food and a meticulous production process. Moreover, due to the development of the Silk Road and cultural exchange between the central plains and Turpan, the diet communication between the central plains and western regions are especially frequent. The phenomenon of dietary Hu Feng in the Tang Dynasty is one of the main examples of Cultural exchange between China and the West and the absorption of foreign culture by Han ethnic group. According to the researches on the diet communication between central plains and western regions, it can be a different perspective to learn about the history and culture of Tang Dynasty. This paper mainly expounds the communication between the Central Plains and Turpan in the Tang Dynasty in terms of diet, which is analyzed and studied from three aspects: the overview of differences, the influence of blending and the possibility and inevitability of cultural exchange. This paper probes into the types and structural differences of staple food and non-staple food between the Central Plains and Turpan. And the spread of Hu food, such as Hu cakes and grapes, in the Central Plains, and the spread of the Central Plains special diet in Turpan. This paper analyzes the blending of food culture from the description of food culture by literati in Tang Dynasty. Finally, it analyzes the possibility and inevitability of food exchange between the Central Plains and Turpan in terms of geographical environment, historical reasons and phenomena.